Performance of Bemisia tabaci MEAM1 and Trialeurodes vaporariorum on Tomato chlorosis virus (ToCV) infected plants - Watanabe, Luís Fernando Maranho [UNESP]; Bello, Vinicius Henrique [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Wiley, 2018)
Whiteflies are important agricultural pests of several crops and cause great economic losses, mainly by the transmission of plant viruses. Among the different species of whiteflies, Trialeurodes vaporariorum and Bemisia tabaci MEAM1 (B biotype) transmit the crinivirus Tomato chlorosis virus (ToCV). Previous studies report that virus-infected plants can influence the attractiveness and the behaviour of different species of whiteflies. In this study, we evaluated the number of eggs, egg hatching rate and emergence of adults of both T. vaporariorum and B. tabaci MEAM1 on ToCV-infected and healthy tomatoes. In addition, ToCV transmission assays were conducted with both whitefly species. ToCV infection did not influence the number of eggs or egg hatching rate of T. vaporariorum; whereas the emergence of adults was reduced by 37.3% on ToCV-infected tomatoes. By contrast, ToCV-infected tomatoes strongly affected the B. tabaci MEAM1 egg hatching rate and emergence of adults with reductions of 41.8% and 92.4%, respectively. Regarding virus transmission, T. vaporariorum transmitted ToCV with lower efficiency (35.7%) than B. tabaci MEAM1 (78.6%). Our data suggest that the performance of T. vaporariorum is less affected than that of B. tabaci MEAM1 when feeding on ToCV-infected tomato plants.
Keywords: adults; crinivirus; development; eggs; transmission; whitefly